2019
DOI: 10.1080/09593330.2019.1651402
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the photoactivity of TiO2 nanoarchitectures doped with cerium or neodymium and application to colour removal from wastewaters

Abstract: The impact of cerium (Ce) and neodymium (Nd) rare-earth metal doping of TiO2 prepared by hydrothermal method was investigated to tailor effective photocatalytic degradation of colored wastewater under UV or visible illumination. The hydrothermal treatment of TiO2 decreased the pHpzc from 6.3 to 3.1-3.8 favoring the affinity for cationic water contaminants. Doping with Ce and Nd modified the crystallinity and the morphology of the photocatalysts and significantly increased the BET surface area and the adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The TiO 2 nanoparticles were prepared using a hydrothermal method. 36,73,74 Briefly, 1 gram of TiO 2 P25 was stirred in 25 mL of 9 M NaOH solution for 1 hour. After 1 hour, the solution was heated in a Teflon autoclave in an oven at 120 °C for 24 hours, followed by centrifugation to remove excess solvent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TiO 2 nanoparticles were prepared using a hydrothermal method. 36,73,74 Briefly, 1 gram of TiO 2 P25 was stirred in 25 mL of 9 M NaOH solution for 1 hour. After 1 hour, the solution was heated in a Teflon autoclave in an oven at 120 °C for 24 hours, followed by centrifugation to remove excess solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The widely used methods are surface modification, 27 doping with metals and non-metals, 24,28–30 creation of oxygen vacancies, 31 and development with other semiconductors. 32,33 Different metals that have been used to modify the optoelectronic properties of TiO 2 include nickel (Ni), 29,30 copper, 34,35 zinc, 34,35 iron (Fe), 36,37 silver (Ag), 34,38 and rare earth metals. 29,30,39–47 Due to its non-toxicity, abundance, and cost-effectiveness, Ni is the most-used dopant for TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, metal and non-metal doping might control the surface area and pores of the particles. Vieira and co-workers [30] have reported that adding 0.5 wt.% Ce and 0.15 wt.% Nd enhanced the catalysts S BET by more than 100%. However, adding more than that is detrimental to the catalyst.…”
Section: Self-dopingmentioning
confidence: 96%
“…In several studies, the surface area and porous structure insignificantly affect the degradation of organic contaminants. For example, according to the findings by Vieira et al [30], the adsorption capacity of Ce-and Nd-TiO 2 photocatalysts were largely influenced by the zeta potential and charge density with a minor influence by the surface area. Meanwhile, Guo et al [42] reported that the degradation of Methylene Blue by S-doped BiVO 4 involved two synergistic factors, which were surface area and S-doping amount.…”
Section: Self-dopingmentioning
confidence: 97%
“…On the other hand, doping with Nd modified the crystallinity and the morphology of the photocatalysts and significantly increased the BET surface area and consequently the adsorption capacity of cationic dyes. The photocatalytic activity under UV light irradiation decreased due to the shielding of the catalyst active area by an excessive amount of adsorbed dye [29]. H. Y.…”
Section: Introductionmentioning
confidence: 99%